Effect of knee pad on kicking a ball and gait analysis - K., Kadirgama; Zahari, Taha; Abdul Rahim, Ismail; Azrul, Hisham; A., Zulkifli; Nasrul Hadi, Johari; Zulfika, Anuar (Ministry of Education Malaysia, 2013)
Wearing kneepads is the best defence against occupational knee injury. It has been reported that the use of knee pads can reduce injuries and increase performance. Knee pads provide protection by disbursing pressure on the knees and preventing puncture wounds. This study focuses on the effect of knee pads on muscle activity and gait analysis. As a case study, measurement of muscle activities whilst kicking a ball was conducted. The normalized mean of the EMG data shows that the vastus lateralis and vastus medialis muscles are highly active when wearing a knee pad.Gait analysis was conducted on six subjects with and without wearing knee pad. Results shows that wearing knee pads increases the force (950 ~ 1150N) acting on the ground, compared with not wearing knee pads (800 ~900 N).